Level of Awareness and Challenges in Republic Act 9184 Procurement Procedures: A Basis for Training and Internal Policy Development - Dagohoy, Abigail Marie V.; Salvatierra, Armelyn C.; Constantino, Ma. Lourdes L.; Matudan, Nhorvic M.; Malang, Bernandino (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
ABSTRACT End-users, who act as the origin of all procurement requests, are responsible for providing technical specifications, scope of work, and terms of reference, conducting a market survey, recommending the Approved Budget for the Contract (ABC), providing technical advice, assisting in the preparation of bidding documents, and attending all stages of the procurement. This study aims to evaluate two essential aspects related to the execution of procurement activities: the level of knowledge and understanding among end-users and the difficulties they encounter while conducting procurement activities. This research used a mixed-methods approach, involving surveys and interviews, to collect data about the awareness levels and difficulties encountered by the participants regarding RA 9184 procurement procedures. In research, "mixed method" refers to a methodology that combines qualitative and quantitative techniques in a single study to gain a more comprehensive understanding of a research issue by harnessing the advantages of both data types. The survey assessed respondents' knowledge of various procurement processes, revealing that they generally have good awareness. Procurement planning was well understood, while document preparation and electronic procurement had slightly lower but still decent awareness levels. Statistical analysis, including Pearson correlation and p-values, showed that awareness was significantly related to years of service in certain procurement aspects but not in post-qualification and awards. Respondents reported occasional difficulties, with the majority having no major issues. However, challenges in areas like canvassing, market study, and document preparation were identified, indicating the need for adjustments or assistance. Other difficulties included a lack of training, technical specification preparation, supplier availability, and failed bidding. In conclusion, policymakers should implement clear procurement request guidelines following RA 9184. These guidelines should specify procedures and required documents, reducing delays and inefficiencies and saving time and resources. Additionally, issuing agency memoranda designating specific End-Users fosters coordination. It serves as a direct point of contact with the BAC Secretariat, ensuring informed Project Management Officers (PMOs) have access to guidance and support. The establishment of a dedicated committee for updating End-Users on specifications and providing annual GPPB-recognized training, which ensures alignment with changing requirements, market conditions, and legal compliance, enhancing procurement efficiency and expertise, should also be imposed.